L’intenzione di curare: utilità dei sistemi diagnostici psicodinamici nella prassi psicoterapeutica - Fagioli, Marcella (Il sogno della farfalla, 2021)
Psychiatry is a branch of medicine. The psychiatrist’s practice requires compliance with the medical methodology: clinical exam, diagnosis and therapy. The intention to cure, which shouldn’t be confused with the concept of taking care, is the driving force moving the doctor’s praxis. In psychiatry, this results to be even more complex since the separation between the intention to cure and the diagnosis turns this latter into a condemn which may also be seen as a moral judgment hiding within it the idea of guilt, evilness, responsibility with the consequent stigma and social exclusion arising as a result. The only possibility to escape from the trap of organicism and psychoanalysis is to consider mental illness as an illness of the unconscious thought: not a behavioral and consciousness related illness but rather an illness of what is not visible such as thoughts and mental images lying behind the perceivable mental reality of words and behavior.